Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation


= √7.-13√7 = -13.7 = -91


And either of their sum or difference = b


= - 6


Thus the two terms are 7 and - 13


Difference = - 13 + 7 = - 6


Product = 7. - 13 = - 91





x(√7 x-13) + √7 (√7 x-13) = 0


(x + √7)(√7 x-13) = 0


(x + √7) = 0 or (√7 x-13) = 0


x = -√7 or x = 13/√7


Roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics